18 comparative aspects between Lean and Six Sigma: Complementarity and implications. Issue 2 (1st June 2015) - Pacheco, Diego; Pergher, Isaac; Vaccaro, Guilherme Luís Roehe; Jung, Carlos Fernando; ten Caten, Carla
Abstract : Purpose: – This paper aims to presents a conceptual comparative analysis of Lean manufacturing and Six Sigma, highlighting 18 critical aspects between such approaches and their respective implications for management decision-making. Design/methodology/approach: – Qualitative approach based on the results obtained from literature review about Lean and Six Sigma. Findings: – The main points of divergence between Lean and Six Sigma have been highlighted based on 18 criteria. Seventeen criteria are proposed as a result of a review of the literature and one criterion, and "quality control", is suggested by the authors. Research limitations/implications: – This article mitigates the literature gap regarding whether and how Lean and Six Sigma are synergistic approaches. Practical implications: – This study enables decision-makers to evaluate the Lean and Six Sigma practices. The results of the analysis performed originated three observations: first, both approaches are predominantly complementary; second, it is possible to create a single model integrating both approaches studied in this research; and third, when Lean is implemented as stand-alone approach, it falls short of specific tools to leverage its full potential according to the complexity of the problem under consideration. Originality/value: – This paper analyzes which aspects from Lean and Six Sigma can be learnt from organizational change and productivity improvement efforts. The analysis includes a comparison of 18 critical aspects for practical use of Lean and Six Sigma.